The question of the Eotriassic tetrapod genus Weltugasaurus in Greenland and thoughts on the fossa coniformis entopherygoidea - Bjerring, H. C. (Meddelelser om Grønland. Geoscience, 1997)
Cranial specimens of Eotriassic tetrapods from central East Greenland which in the mid-1930s were assigned to the genus Wetlugasaurus have been re-examined and found to represent a new, capitosaur-like genus, named Selenocara. A cone-shaped fossa in the entopterygoid bone is the focus of particular attention. This depression appears to have engaged with the affacial process and not, as has often been maintained, with the basipterygoid process. The consequences of this reinterpretation of the fossa coniformis entopterygo idea are far-reaching, and some of them are, to an extent, discussed herein.